The impact of macroeconomic variables on foreign direct investment (fdi) in asean-5 countries - Chong, Fong Yi (2023)
The past decades, the ASEAN has grown to be an important economic player. The foreign direct investment (FDI) inflows play an important role in achieving ASEAN’s economic development. The ASEAN-5 is the biggest consumer market of the world after China and India. Hence, this study aims to investigate the impact of macroeconomic variables on FDI inflows in ASEAN-5 countries (Indonesia, Malaysia, Philippines, Singapore, and Thailand) for the period 1970-2018. Using five explanatory variables (market size, inflation rate, trade openness, exchange rate and oil prices), this study tries to investigate the factors that determine FDI inflows to the studied countries. To achieve this objective, this study will utilise Autoregressive Distributed Lag (ARDL) approaches to investigate the long run relationship between the explanatory variables and FDI inflows. Based on a comparative discussion, the study results will demonstrate what are the common factors will attract or discourage FDI inflows into the ASEAN-5 countries. The findings revealed that there is a mixed results in terms of the main determinants of FDI as well as the direction of relationship. Market size as measured by Gross Domestic Product (GDP), inflation and exchange rates are significant in most of the sample countries. Meanwhile, only in Thailand the trade openness has a significant relationship with FDI whilst oil price has a significant relationship with FDI in the Philippines. Further analysis revealed that GDP has a positive relationship with FDI implying that the bigger size of the country market, the higher the FDI inflows into the country. Meanwhile, inflation rate and exchange rate showed a mixed direction of relationship among the sample countries. This study has significant implications for body of knowledge and practitioners. The findings in the study help to further understand the multiple factors influencing FDI in ASEAN-5 countries which has not been extensively investigated. Meanwhile, policymakers from the sample countries would be able to understand the importance of the main determinants of FDI inflows to their respective countries. Hence, steps could be taken to utilize the factors to attract the FDI inflows. The insignificant of trade openness and oil price as FDI drivers in most of sample countries has opened new insight on measurement of the variables and methods of analysis for future research.